CRIMINAL LIABILITY AGAINST PERPETRATORS OF FRAUDULENT CRIMINAL ACT BY HYNOSIS - Rusdi, Puspitasari; Muhadar, Muhadar; Haeranah, Haeranah (Tadulako Law Review, 2020)
Crimes by hypnosis are very common among the people. Hypnosis is a type of crime. This crime is also difficult to uncover because it has minimal evidence. This hypnotic crime needs to be included in the law as a criminal offense, because this crime is directly felt by the public. the method used is normative law by using several approaches namely the statute approach, the case approach, the comparative approach and the conceptual approach. A person who commits a criminal offense and has an error, then the person will be convicted. A criminal offense that can be accounted for is included in the element of intent or negligence / negligence. The act can be accounted for if the maker requires the condition, that the person who committed the criminal act had an error. then the defendant must use the theory of purpose of punishment which is appropriate for the perpetrators of criminal fraud by hypnosis. Crimes with hypnotic acts can be subject to fraud offenses. This is because the hypnotic act is intended to take advantage of the victim, using actions that move others to do something. Fraud crime is regulated in Article 378 of the Criminal Code, in an act of hypnosis the aim is to move others to give up something, to benefit themselves. Moving it is done by deception or a series of lies, which makes the victim do something. So the element of purpose and element of the way in this case meets to be categorized as fraud offense, so that hypnosis can be snared with the article fraud